1988
DOI: 10.1111/j.1559-1816.1988.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Socializing Attribution: Generalization to “Real” Social Environments1

Abstract: Social status variables have been shown to influence attributional judgments, but their effects have been demonstrated almost entirely in experimental settings. The influence of such statuses in experimental settings may differ from their influence in natural settings. We examined the influence on attributional judgments of the status characteristics of both subjects and actors in conjunction with variations in the degree of “real world” characteristics of both subjects and social context. These comparisons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This included such statements as childhood experiences, history of crime, social environment, lack of concern for others, emphasis on power/money, personality, and 6) Attribution measure -A series of attribution questions was generated which addressed a broad range of internal and external causes of crime. Several questions were adopted from previous research studies in which these legal attitudes were found to be predictive of predeliberation verdict preferences (Carroll, Perkowitz, Lurigio, & Weaver, 1987;Howard & Leber, 1988). More specifically, two general areas are presented: social/economic and personal.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…This included such statements as childhood experiences, history of crime, social environment, lack of concern for others, emphasis on power/money, personality, and 6) Attribution measure -A series of attribution questions was generated which addressed a broad range of internal and external causes of crime. Several questions were adopted from previous research studies in which these legal attitudes were found to be predictive of predeliberation verdict preferences (Carroll, Perkowitz, Lurigio, & Weaver, 1987;Howard & Leber, 1988). More specifically, two general areas are presented: social/economic and personal.…”
Section: Dependent Measuresmentioning
confidence: 99%